The Use of Google Drive to Improve Student’s Essay Writing Skill, Faculty of Teacher Training and Education, Pancasakti University of Tegal - Nur Aflahatun; Yoga Prihatin (Cakrawala: Jurnal Pendidikan, 2018)
This experimental research employs true-experimental design with two-group design type (experimental group and control group) and takes 48 fourth-semester English Education students of the academic year 2017/2018 of the Faculty of Teachers Training and Education, Pancasakti University, Tegal as its samples, divided into 2 (two) groups: experiment group with 24 students and control group with 24 students. The research employs t-test for effectiveness test as its data analysis technique. The research results show that the usage of Google Drive based learning model effectively improves students’ essay writing skill. The Google Drive based learning media can be applied to academic writing learning process, particularly essay, however, its practice requires intensive interaction between students and lecturer.